Ontic Structural Realism: Relations without relata? (Culturas Científicas, 2018)
The aim of this work is to study the ontological thesis defended by Ontic Structural Realism, which, in general, states that the ontological commitments should be focused in the relations and not on objects. This would be a more coherent realist stance towards modern physical theories. In first place we will study the ontological conception defended by the Ontic Structural Realism, which, broadly speaking, postulates that the ontological focus should be placed on relations rather than on objects. This, in turn, would constitute a realistic interpretation of the current physical theories. Secondly, as a possible defense to the position stated by Ontic Structural Realism, the concept of non-supervenient relations will be studied and it will be argued that it is this type of relations that acquires a fundamental character in Quantum Mechanics, as, for example, in phenomena such as the so-called quantum entanglement.